Therapeutic effects of Caesalpinia minax Hance on complete Freund's adjuvant (CFA)-induced arthritis and the anti-inflammatory activity of cassane diterpenes as main active components. (15th November 2018) - Tong, Ziwei; Cheng, Li; Song, Jizhou; Wang, Miao; Yuan, Jiuzhi; Li, Xianzhe; Gao, Huiyuan; Wu, Zhaohua
Abstract: Ethnopharmacological relevance: Seeds of Caesalpinia minax Hance called 'Ku-Shi-Lian' (KSL) in China have been used as Zhuang or Dai folk medicines for treatment of common cold, fever, rheumatoid arthritis and dysentery for hundred years. Aim of the study: This study aimed to investigate therapeutic efficacy of KSL extract using complete Freund's adjuvant (CFA) induced arthritis in a rat model and the anti-inflammatory activity of cassane diterpenes as the main active material basis of this herb. Materials and methods: Arthritis was induced in male Wistar rats (200–220 g) by immunization with CFA. Dexamethasone (DXMS) and Tripterygium glycosides (TG) were chosen as the positive drugs. Water soluble fraction (CMW, 1000 and 2000 mg/kg) and chloroform soluble fraction (CMC, 400 and 800 mg/kg) of KSL were orally administered from day 1 and continued for 21 days. Change of paw swelling perimeter, arthritics score, body weight growth, were observed, and the production of TNF-α, IL-1β and IL-6 in serum were measured by enzyme-linked immunosorbent assay (ELISA). The histological changes in the ankle joint were analyzed in adjuvant induced arthritis rats. Moreover, the inhibitory effect on mRNA expression of proinflammatory cytokine IL-1β, IL-6 and TNF-α of fourteen cassane diterpenes obtained from CMC extract were valued using the RAW 264.7 macrophages cell stimulated by lipopolysaccharide (LPS) assay. Results: The chloroform soluble fraction (CMC) showed the significantly suppressed change of paw swelling perimeter, arthritics score and increased body weight loss. The overproduction of TNF-α, IL-1 β and IL-6 were remarkably suppressed in the serum. Fourteen cassane derivatives as the main constituents of CMC extract showed the promising activity on the expression mRNA of cytokine IL-1β, IL-6 and TNF-α produced by macrophages cells. Conclusions: In this study, the chloroform soluble fraction of 'KSL' (seeds of C. minax ) was found to exert an anti-RA activity significantly in vivo for the first time, which indicted this fraction might be used as a powerful therapeutic agent for arthritis treatments. Cassane diterpenes, as the main constituents in this fraction, showed the anti-inflammation activity through the regulation of cytokine expression, which might be developed as target-agents for this national herb further developing. Graphical abstract: